2014
DOI: 10.4236/fns.2014.55053
|View full text |Cite
|
Sign up to set email alerts
|

Catechin and Epicatechin Contents in Wines Obtained from Brazilian Exotic Tropical Fruits

Abstract: Flavonoids constitute a diverse group of secondary metabolites which are present in both fruits and wines. The contents of some of the most prominent compounds such as catechin and epicatechin are little known in wines prepared from tropical fruits. In this context, this study was aimed to determine catechin and epicatechin contents in wines processed from 7 tropical fruits (cajá-umbu, cashew apple, mangaba, pineapple, siriguela, sugar apple and umbu), by HPLC-DAD system. Moreover the total phenolic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Moreover, catechins are abundantly found in the beverages such as green tea and apple wine, and exhibit multiple biological activities [37,38]. The findings of the present study was in accordance with the recent report on fruit wines by Ramalho et al [42] wherein their study revealed the occurrence of catechin and epicatechin among fruit wines, was comparatively higher than grape wines. The antioxidant profile of Flacourtia montana wine was on par with the Jackfruit (Artocarpus heterophyllus Lam.)…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, catechins are abundantly found in the beverages such as green tea and apple wine, and exhibit multiple biological activities [37,38]. The findings of the present study was in accordance with the recent report on fruit wines by Ramalho et al [42] wherein their study revealed the occurrence of catechin and epicatechin among fruit wines, was comparatively higher than grape wines. The antioxidant profile of Flacourtia montana wine was on par with the Jackfruit (Artocarpus heterophyllus Lam.)…”
Section: Discussionsupporting
confidence: 93%
“…Ramalho and others () have reported the presence of catechin and epicatechin (4.34 and 4.11 mg/L, respectively) in A. squamosa wine. Also, the bitterness in wines is due to the flavan‐3‐ols catechin and epicatechin (Nobel, ).…”
Section: Resultsmentioning
confidence: 92%
“…In addition, tannins can be formed by polymerising flavonoid derivatives such as flavane-3-ol and flavane-3,4-diol. The most important representatives of flavane-3-ols are catechins and epicatechins, which contribute to the retention of taste, astringency, and texture characteristics during wine aging [ 80 ]. However, the concentration of catechin and epicatechin in all wines has been reported to decrease during aging [ 74 ].…”
Section: Non-volatile Mouth-feel Compounds Are Altered During Bottle ...mentioning
confidence: 99%